Des jardins ouvriers au jardinage de rue : pour une géohistoire des jardins collectifs à Marseille - Jean Noël Consalès (In Situ)
Based on an analysis of historical archives and long-term monitoring of the situation in the city, this article proposes a geo-historical interpretation of collective gardens in Marseille. It identifies the ideas that, at national and local levels, bring about the changes in these gardens, the stakeholders who are involved in them and the urban spaces that are designated for them. The first part of the article comprises a study of the territorial process whereby workers’ allotments located in the agricultural suburbs of the early twentieth-century city tend to become family gardens subjected to all the real estate pressures of today’s residential suburbs. In a second part, the article gives an account of the diversification of collective gardens with a notable development of community gardens and street gardening. Finally, it wonders what sort of heritage status might be attributed to the city’s twelve family allotment gardens and fifty or so shared community gardens.